2020
DOI: 10.1177/2325967120s00104
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurement of Caucasian and Asian Knees, Mismatch with Knee Systems?

Abstract: Background: Positioning and fit of the knee prostheses in patients determines functional outcome. For that matter anthropometric differences between knee joints of patients, will affect function. Since most total knees implant systems are designed for caucasians, discrepancies in matching to Asian patients might exist, with consequently less optimal fit of the implant. The aim of this study was to evaluate differences in anthropometric dimensions between Caucasian and Asian knees of patients eligible for total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recent articles have shown that anteroposterior to mediolateral femoral and tibial ratios differ between ethnic groups and that component overhang might lead to knee pain [11][12][13]36]. CIM implants provide better cortical bone coverage and thus reduce the risk of overhang and undercoverage [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent articles have shown that anteroposterior to mediolateral femoral and tibial ratios differ between ethnic groups and that component overhang might lead to knee pain [11][12][13]36]. CIM implants provide better cortical bone coverage and thus reduce the risk of overhang and undercoverage [37].…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that the overall coronal lower limb alignment should not only be classified in neutral, varus or valgus on the basis of the hip-knee-ankle angle (HKA), but that femoral and tibial joint lines should be considered as well. Furthermore, several studies have demonstrated that among different ethnic groups different mediolateral-to-anteroposterior ratio of tibia and femur exist [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, to fit the morphology of each knee, surgeons mainly use conventional, off-the-shelf implants, which come in different sizes and models. These implants are based on standardized anthropometric measurements, which cannot take into account all individual characteristics [ 14 , 15 ]. To address this issue, CIs were developed using 3D-printing technology.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially relevant approach to improve the outcome after knee arthroplasty, which besides enhancing surgical precision and defining an optimal alignment strategy, consists of developing new implant designs. Conventional, off-the-shelf (OTS) implants were developed on the basis of anthropometric measurements of a defined standard population [ 13 ]. Although different models and sizes of OTS implants exist, it can be challenging to find the best fitting implant design and size for the individual patient’s knee morphology.…”
Section: Introductionmentioning
confidence: 99%